Bridging the Justice Gap: A Study on the Challenges and Solutions for Legal Aid in Indonesia - Suteki Suteki; Abdul Jalil; Aga Natalis; Evis Garunja (Indonesian Journal of Advocacy and Legal Services, 2026)
Legal aid represents an essential tool for ensuring access to justice for all citizens, particularly the impoverished who are frequently marginalised by prohibitive costs and limited legal knowledge. Under Law No. 16 of 2011 on Legal Aid, the Indonesian state formally guarantees the right to free legal aid for the poor. In practice, however, the implementation of legal aid faces various challenges. These include uneven dissemination of information, budget limitations, and a reimbursement-based funding system that obstructs smooth operations. Furthermore, administrative difficulties continue to act as barrier to those seeking legal services. This study adopts a socio-legal approach, combining two types of research: doctrinal legal research to examine the normative aspects of the law, and empirical social research focused on data collection through interviews and field observations related to social phenomena in the provision of legal aid. The method employs descriptive analysis to scrutinise  and interpret the collected data, as well as identify factors affecting the effectiveness of legal aid implementation in Indonesia. Based on research in Pontianak and Bogor, this study identifies that the main obstacles to providing legal aid include the poor understanding of their rights among the poor and the unequal distribution of legal aid in remote areas. Consequently, this study proposes several strategies interventions to improve the effectiveness of legal aid – such as strengthening broader and more systematic outreach, improving a more flexible funding system, enhancing the capacity of legal aid institutions, and utilising information technology to expand public access to legal aid services.